2014
DOI: 10.1128/jvi.03628-13
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Derepression of the ERVWE1 Locus following Influenza A Virus Infection

Abstract: Syncytin-1, a fusogenic protein encoded by a human endogenous retrovirus of the W family (HERV-W) element (ERVWE1), is expressed in the syncytiotrophoblast layer of the placenta. This locus is transcriptionally repressed in adult tissues through promoter CpG methylation and suppressive histone modifications. Whereas syncytin-1 appears to be crucial for the development and functioning of the human placenta, its ectopic expression has been associated with pathological conditions, such as multiple sclerosis and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 66 publications
1
48
0
Order By: Relevance
“…Elements with intact long terminal repeats as well as those elements flanked by truncated long terminal repeats were expressed and regulated secondary to the virus infection. Findings recently reported by Li et al 66 suggest that an exogenous influenza A virus infection can transactivate HERV-W element ERVWE1 by increasing the transcription of GCM1 and reducing the repressive histone mark H3K9me3 in this region and in other regions harboring HERV-W elements. Perron et al 67 demonstrated that in vitro infection of leptomeningeal cells in patients with multiple sclerosis with herpes simplex virus type 1 results in potent stimulation of the specific reverse transcriptase activity and coexpression of both herpes simplex virus type 1 virions and retrovirus-like particles.…”
Section: Herv-w Activation By Infectionsmentioning
confidence: 95%
“…Elements with intact long terminal repeats as well as those elements flanked by truncated long terminal repeats were expressed and regulated secondary to the virus infection. Findings recently reported by Li et al 66 suggest that an exogenous influenza A virus infection can transactivate HERV-W element ERVWE1 by increasing the transcription of GCM1 and reducing the repressive histone mark H3K9me3 in this region and in other regions harboring HERV-W elements. Perron et al 67 demonstrated that in vitro infection of leptomeningeal cells in patients with multiple sclerosis with herpes simplex virus type 1 results in potent stimulation of the specific reverse transcriptase activity and coexpression of both herpes simplex virus type 1 virions and retrovirus-like particles.…”
Section: Herv-w Activation By Infectionsmentioning
confidence: 95%
“…Flow cytometry data showed increased percentages of cells exposing surface HERV-W (ERVW-1) Env protein, that occur differently in specific cell subsets, and in acute disease and past infection [174]. Expression of the same retroviral protein was considerably increased in various human cell types following influenza A virus infection [2]. Importantly, treatment with neuroleptics and antidepressants (e.g., valproic acid, haloperidol, risperidone, and clozapine) may greatly upregulate the expression of HERV-W (ERVW-1) and ERV9 elements in CNS cells [176].…”
Section: Neurological Diseasesmentioning
confidence: 96%
“…Genomic copies of HERVs are of particular interest because in addition to functional viral genes, they have multitude of regulatory DNA regions serving as promoters [1][2][3], enhancers [4,5], polyadenylation signals [6,7], insulators [8,9] and binding sites for various nuclear proteins [2,[10][11][12][13]. Many families of HERVs exhibit high transcriptional activity in human tissues [1,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Certain copies of the HERV elements are activated by some infectious agents. For example, T. gondii and the influenza virus may activate HERV-W elements within human cell lines (Frank et al, 2006; Li et al, 2014; Nellaker et al, 2006). Several studies including a meta-analysis have indicated an increased prevalence of antibodies against T. gondii in schizophrenia (Torrey et al, 2007, 2012).…”
Section: Infection Induced Activation Of Hervsmentioning
confidence: 99%